El arte como dispositivo político: diálogos transnacionales en la promoción y censura de los murales de ignacio gómez jaramillo en el Capitolio Nacional (2020)
In 1949, the Ninth Pan American Conference was held in Bogotá, which had as one of its main objectives the inauguration of the Organization of American States (OAS). The organization of the event, which would take place in the National Capitol of Colombia, was delegated to the conservative leader Laureano Gómez. Within the adaptation plans of the Capitol for the event, by the order of Gómez, the two murals that were part of the building?s ornamentation were covered. These murals are La liberación de los esclavos and La Rebelión de los comuneros, both from 1938 by the Colombian artist Ignacio Gómez Jaramillo. Given its strong political content and the evident influence of Mexican muralism, an act of censorship was committed. With that in mind, this investigation studies the reasons behind the decision of covering up the murals, taking into account the political disputes in the arts from the end of the 19th century to the middle of the 20th century under the theoretical lens of transnationalism. We looked for the relations of Colombia in the artistic, political, economic, cultural and social fields with Mexico, Latin America, Paris, Madrid, Moscow and Berlin in order to contextualize and conceptualize the appearance of these peculiar artworks in the Capitol and their censorship.